Assessing and managing hallucinations in children and adolescents. (November 2016) - Dominguez, Maria-De-Gracia; Garralda, M. Elena
Summary: Hallucinations (erroneous percepts in the absence of identifiable stimuli) are a key feature of psychotic states, but they have long been known to present in children with non-psychotic psychiatric disorders. Recent epidemiological studies of child populations found surprisingly high rates (about 10%) of hallucinatory experiences. These hallucinatory phenomena are most likely to occur in the absence of psychiatric disorder and are usually simpler, less elaborate and less distressing than those observed in children with psychiatric disorders. This article details the clinical assessment of hallucinations in children and adolescents, taking into account developmental considerations and paediatric organic associations. It describes hallucinations in young people with psychoses (schizophrenia spectrum and mood disorders) and non-psychotic psychiatric disorders (emotional and behavioural disorders), and it addresses therapeutic aspects.